ETIKA BISNIS ISLAMI DALAM PERIKLANAN - Amelia Rahmaniah (Millah: Journal of Religious Studies, 2009)
As a bridge between producers and consumers, advertisement has a very strategic  position from business point of view, since it can present complete and accurate information to the consumer about the product or service. Therefore, the advertisement should be paid attention seriously in Islamic business ethics. Advertisement that does not use ethics will damage the corporate image; and gradually the company may be unseen by the consumer. On the other hand, doe consumer may also have bad consequences. Thus, advertisement should have the following ethics, i.e. conveying true and complete information, not containing elements of  coercion, are not in conflict with the values decency, addressing to the proper targets and not providing the sample that may endanger public.